Anticoagulant use in atrial fibrillation and risk of dementia: review of contemporary knowledge. (2nd December 2017) - Jacobs, Victoria; Graves, Kevin G.; Bunch, Thomas J.
ABSTRACT: Introduction : Atrial fibrillation (AF) is strongly associated with dementia, including idiopathic dementias such as Alzheimer's disease. The relative risk of dementia is highest in AF patients 70 years and younger, and the burden of exposure to arrhythmia appears to underlie part of the risk. Areas covered : Anticoagulation choices and approach influence dementia risk. In warfarin patients, inadequate time spent in therapeutic range is highly associated with the increased dementia risk long-term. This risk is further accentuated with frequent over anticoagulation in patients also receiving aspirin. Direct oral anticoagulant therapies in early observational studies show that there is potential for improving long-term risk of dementia when compared to warfarin, although prospective trials are needed. AF and dementia are end manifestations of systemic disease; a systemic approach is needed with early treatment of shared risk factors to prevent disease presentation altogether. Expert commentary : In this review, we will bring together available data with regards to the link between anticoagulant use for AF and dementia. Anticoagulation initiation timing, use, and efficacy remain critical risk factors for dementia in AF patients and consequently provide opportunities to decrease risk.